Clear Cell Sarcoma of the Foot in an 18-Year-Old Female - Marwan A. Albeshri; A. Ashour (Case Reports in Orthopedics)
We report a case of an 18-year-old female without a relevant medical history who presented with an 8-month history of a left foot mass. It started as a small nodule that progressively increased in size over time. The mass then became ulcerative with foul-smelling discharge. There was no palpable left inguinal or other lymph nodes upon physical examination. Histological examination of the biopsy confirmed a diagnosis of clear cell sarcoma. Clear cell sarcoma is a rare soft tissue neoplasm. However, early diagnosis is crucial to prevent metastasis and worsened prognosis. Clear cell sarcoma has an extremely poor prognosis once metastasis occurs, and to the best of our knowledge, only fewer than 100 cases have been reported in the literature.